بەراوردی چەند تایبەتمەندیيەکی ستایڵی شیعریی مەولەوی ڕۆمی و مەولەوی تاوگۆزی - تەها, پ.ی.د.عەدنان عەبدولڕەحمان; حەمەکەریم, پ.ی.د سەبور عەبدولکەریم (Sulaimani Journal for Humanities, 2023)
This research aims at introducing the poetic style of both poets who have the same poetic nickname. Eventhough they belong to two different nations, different languages and different eras. (Tawgozi) lived five centuries after (Rumi) and was aware of his works. The basic question is as they have a common intellectual sources such as (Islam, Mysticism, Discourse, …..) which gives them a rather similar vision. In practice, to what extent they have produced poetic texts and more importantly their stylistic expression of that mindset is similar. And to what extent the second poet can have his own independent style. Answering that question would be very difficult without a having a framework and its own limits. Therefore, a topic that is of concern for both poets (the spring nature) is used. Three of the most important poems of both poets are selected. In light of analysing and comparing those six texts in three levels of language, thought and literary are described according to importance not a fix classification. To a suitable level the scientific aim of the research is achieved and in conclusion (13) identical points and (17) different points are discovered in their style. The reader should first read the six texted in the appendix before reading the research. The research consists of abstract, introduction and two sections which describe the similarities and differences of both poets’ styles and conclusion and the list of references.
Keywords: Keywords comparison; poetic style; Mollavi Romi; Mollavi Tavgozi